Fischer-Tropsch synthesis on Pd-Co/Nb2O5 catalyst - Souza, Carlos Darlan de (2007)
Cobalt-based catalysts have been widely used in the CO + H2 reaction for hydrocarbons production; they are among several others to produce hydrocarbons from CO hydrogenation because of their ability to hydrogenate dissociated carbon species and promote chain growth. Cobalt is a typical metal that may adsorb CO molecules dissociatively forming carbon atoms at the surface, which may be hydrogenated, and it is an appropriate catalyst for the formation of long-chain hydrocarbons. However, the main problem of the Fischer–Tropsch synthesis (FTS) is the wide range of product distribution when conventional Fischer–Tropsch catalysts are being used. To overcome the selectivity limitations and enhance the catalyst efficiency in CO hydrogenation, several approaches have been studied such as the use of reducible supports and the addition of a second metal component. This chapter investigates the performance of the bimetallic Pd-Co/niobia systems in CO hydrogenation reaction to explain the effect of a second metal on the product selectivity of Co-based catalysts compared to the Co/Nb2O5 systems.